Between accumulation and (in)security: The real estate industry and the housing crisis in Egypt - Mokhtar, Norhan Sherif (AUC Knowledge Fountain, 2017)
Despite the turmoil and instability triggered by the Egyptian Revolution in 2011, the real estate market has remained relatively stable. According to the Ministry of Investment, real estate has witnessed a noticeable growth â€œdespite political instabilityâ€ , and government figures show that the real estate sector has become the second largest sector in receipt of public and private investments beginning from the financial year (FY) of 2010/2011, with 14% of total investments, a figure that grew by FY of 2011/2012 to reach 16.3% . For the following financial years, albeit slowing down in pace, real estate continued to be the second largest sector to receive investments . The research investigates the pursuit of financial security through property and land ownership in Egypt, and how it serves as a paradoxical representation of Egyptiansâ€™ insecurities and fears reflecting the precarious nature of their lives, specifically through looking at how housing as a social project has become commodified through the real estate business. This thesis looks at the economic and political factors which led to the financialization of peopleâ€™s lives and in turn the dismantling of housing as a social project. What thus becomes the role of the state in producing speculation as an aspiration of citizens particularly the professional middle class? I seek to explore the question of how this relates to different aspects of social and economic rights. Studying the real estate industry and the actors involved and understanding its everyday politics will allow me to understand the economy of speculation which has come to govern and shape our lives and imaginations, driving urban Cairo to become transformed into a market. Looking at the practice of â€œinvesting in housingâ€ allows me to see the cultural manifestations of economic and political phenomenon which gave way to the financialization of peopleâ€™ lives in the everyday lives of people.